Synthesis, Characterization and Antibacterial Activity of 2-[(Substituted phenyl)]-3-[(2-methyl-4-thiazolyl)acetamido]-Thiazolidin-4-Ones - Krishna Rao, Gopal; P. Chakraborty, Suvadip; Sanjay Pai, P.N.; Srinivasa Murty, M. (Asian Journal of Chemistry, 2016)
2-[(Substituted phenyl)]-3-[(2-methyl-4-thiazolyl)acetamido]thiazolidin-4-ones were synthesized by reacting the Schiff’s bases of 2-methylthiazole-4-acetic acid hydrazide with thioglycolic acid. The title compounds were characterized by spectral data and were screened for antibacterial activity. Some of these thiazolidinones show promising activity.